Gambaran Pelaksanaan Perawatan Luka Operasi Pasien Post Sectio Caesarea di Bangsal Sakinah RS PKU Muhammadiyah Yogyakarta - Dewi, Vivi Yanti Mala (STIKES 'Aisyiyah Yogyakarta, 2008)
Lately Section Caesarea (SC) had been famous because most of people think that simple method and it doesn’t make hurt. Injury Treatment is which one external factor has good supported and influential of injury treatment processed and to avoid risk happened as like complex operat ion injury infection (ILO). Taking injury treatment with true way in standard operational procedure (SOP) is which one effort to be good nurse services in hospital so people judge the quality health services that better. This experiment purpose to obtain illustrations about carrying out of section caesarea operation injury treatment post patient in class Sakinah PKU Muhamadiyah Yogyakarta Hospital. The research of method use quantitative research which observational descriptive character with prospective s tudy approach. Total samples amount 14 respondents and observation injury treatment have done at 3 th operations post. The result of observation to 28 actions injury treatment from 14 respondents, 100% as sufficient category at all and result every single stage is : 1) 92,9% pre interaction stage included good category, 7,1% sufficient; 2) 64,3% good orientation stage, 35,7% sufficient; 3) 78,6% poor work stage, 21,4% bad; 4) 64,3% good termination stage, 35,7% sufficient; 5)100% good documentation stage. Illustrations about carrying out of section caesarea operation injury treatment post patient in class Sakinah PKU Muhamadiyah Yogyakarta Hospital at 2008 which 100% as sufficient category at all with 5 stages are: pre interaction, orientation, work, termination and documentation. This result of research has to think over especially TIM ISO 9001:2000 PKU Muhamadiyah Yogyakarta Hospital at 2008 for arranging nurse upbringing that post operation SC case, and fixed procedure for injury treatment in work stage delve into dirty injury treatment and clean are more important.